Efectividad de Bupivacaína isobarica 0,2% vs 0.3% asociada a fentanilo en anestesia subaracnoidea para cesáreas, Hospital Regional de Loreto, 2022 - Huayanay Viera, Johssy Aquila (2024)
The technique of choice in cesarean sections is subarachnoid anesthesia, innovations have been made by using the dilutional technique, as well as the use of low doses of local anesthetics associated with intrathecal opioids for the advantages they offer by promoting rapid recovery of the patient and decreasing the frequency of occurrence of adverse effects. OBJECTIVE: To compare the effectiveness of isobaric bupivacaine 0.2% vs 0.3% associated with fentanyl in subarachnoid anesthesia for cesarean section at the Loreto Regional Hospital 2022. METHODS: Randomized retrospective controlled experimental study at the Regional Hospital of Loreto during the period January-December 2022, the sample will consist of a total of 56 patients divided into two groups who will undergo cesarean section. The technique to be used will be randomly assigned to each patient who meets the inclusion criteria; group 1 will be administered bupivacaine 0.2% and group 2 bupivacaine 0.3%, both concentrations associated with fentanyl. For the bivariate analysis of hemodynamic changes in both groups, the statistical significance of the values of blood pressure, heart rate and oxygen saturation recorded at different times will be analyzed and processed with the Kruskal-Wallis nonparametric test; the Chi-square test will be used to evaluate the relationship between onset time, latency time, total anesthesia time, level of sensory and motor blockade. Statistical tests will be significant at a value of p < 0.05.